2012
DOI: 10.1007/s12094-012-0855-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of annexin A2 and cancers

Abstract: Annexins are a group of calcium- and phospholipid-dependent proteins. As a member of the annexin, annexin A2 (Anxa2) is widely distributed in nucleus, cytoplasm and extracellular surface and mainly expressed in human endothelial cells, mononuclear cells, macrophages, marrow cells and some tumor cells. Accumulated evidences indicated that Anxa2 deregulation was associated with the occurrence, invasion and metastasis of cancers. Anxa2 up-regulation was related to the development, invasion, metastasis and drug re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“…Furthermore, it has been suggested that Annexin A2 may be used as a potential biomarker for the diagnosis, treatment and prognosis of tumors (18). Zhang et al (18) reported that the soluble Annexin A2 concentration detected by ELISA in serum samples from 42 patients with lung cancer was significantly higher than in 43 healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that Annexin A2 may be used as a potential biomarker for the diagnosis, treatment and prognosis of tumors (18). Zhang et al (18) reported that the soluble Annexin A2 concentration detected by ELISA in serum samples from 42 patients with lung cancer was significantly higher than in 43 healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer cells, abnormal expression of ANXA2 has been associated with cancer progression and metastasis (17,(36)(37)(38). One study has indicated that ANXA2 promotes cancer cell migration and invasion via F-actin polymerization change of the microstructures in cancer cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…ANXA2 is a direct and functional target of KMT1E in lung cancer cell metastasis Previous studies have shown that the calcium-dependent phospholipid-binding protein ANXA2 plays a role in F-actin polymerization (24) and cancer metastasis (17). To examine whether ANXA2 plays a role in lung cancer, we performed Factin staining and in vitro invasion assays.…”
Section: Kmt1e Acts As a Crucial Repressor For Cellular Metastasis Inmentioning
confidence: 99%
See 1 more Smart Citation
“…The combined exposure of prepubertal rats to Bisphenol A and genistein increases annexin A2 levels in mammary gland by 73%, whereas genistein alone decreases it by 67% [8]. It is known that both increased and decreased levels of annexin A2 increase cancer risk [38,8,39]. Environmental mixtures of EDC which affect different pathways are difficult to investigate with standard toxicology methods; however, the use of bioinformatics and systems biology may dramatically improve risk assessment of combine exposures [40].…”
Section: The Xenostrogens and Cancer Riskmentioning
confidence: 99%